Agropolitana: Countryside and Urban Sprawl in the Veneto Region (Italy) - Ferrario, Viviana (Journal for Geography, 2009)
In the Veneto central plane, historically shaped by agriculture, the countryside is being taken over by a particular form of urban sprawl, called città diffusa (dispersed city), where cities, villages, single houses and industries live alongside agriculture. This phenomenon is generally analyzed mainly as a typical urban/rural conflict, and the sprawl gets criticized as a countryside destroyer.By observing some paradoxical situations in the città diffusa in Veneto, the contrary is apparent – urban sprawl seems to have been rather a conservation factor for the ecological and cultural richness of the agricultural space. Agricultural space itself plays an important multifunctional role in this territory. If seen from this point of view, dispersed urbanization in the Veneto region can be seen as a sort of prototype of a new contemporary form - neither urban nor rural – of cultural landscape, where farming spaces can have a public role strictly linked to the urban population's needs. Can this character be preserved through the metropolization process now envisaged by regional policy and planning, and already happening? Can the “Agropolitana” concept introduced by the new Regional Spatial Plan help to imagine and obtain a resilient metropolis, while maintaining a strong agricultural layer inside it?